Pengaruh Kompetensi terhadap Efektivitas Kerja Pegawai Sekretariat DPRD Kota Tasikmalaya - Desri Mulianti (Fenery Library, 2022)
This research is based on the author's initial findings related to the ineffective performance of employees at the DPRD Secretariat of Tasikmalaya City, with the results of the SAKIP assessment for 2020 for indicators of financial governance assessment and regional apparatus performance in 2020 only reaching a value of 62.45 from the target value of 71.00 . The level of responsibility at work is still not maximized, this can be seen from the SAKIP assessment for 2020, where the realization of the budget for direct expenditures has only been absorbed by 90% for 54 activities. This is suspected to be related to the competence of employees who are still not optimal. The purpose of this study was to determine how much influence competence has on work effectiveness at the Secretariat of DPRD Tasikmalaya City. The research method used is explanatory research with a quantitative approach. Data collection techniques used are documentation studies and field studies conducted through observation and distributing questionnaires to 54 respondents, while data analysis uses simple linear regression analysis, this is because there is only one independent variable, namely employee competence. The results of the study obtained data that competence affects work effectiveness by 65% and the remaining 35% is influenced by other variables not examined. The dimension of competence that has the greatest influence on work effectiveness is the attitude dimension.